Proceedings of the 3rd Workshop on Emotions and Personality in Personalized Systems 2015 2015
DOI: 10.1145/2809643.2809644
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Personality Traits with Instagram Pictures

Abstract: Instagram is a popular social networking application, which allows photo-sharing and applying different photo filters to adjust the appearance of a picture. By applying photo filters, users are able to create a style that they want to express to their audience. In this study we tried to infer personality traits from the way users take pictures and apply filters to them. To investigate this relationship, we conducted an online survey where we asked participants to fill in a personality questionnaire, and grant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 12 publications
2
33
0
5
Order By: Relevance
“…There is an increasing body of work that looks at how to implicitly acquire personality traits of users. Since all kind of information can relate to personality traits, even information that is not directly relevant for a specific purpose may still contain information that is useful for the extraction of personality (e.g., Facebook [8], Twitter [25,27], and Instagram [10,11]). The increased connectedness between SNSs and applications through SSO buttons provide an abundance of information that can be exploited to implicitly acquire personality traits of users.…”
Section: Related Workmentioning
confidence: 99%
“…There is an increasing body of work that looks at how to implicitly acquire personality traits of users. Since all kind of information can relate to personality traits, even information that is not directly relevant for a specific purpose may still contain information that is useful for the extraction of personality (e.g., Facebook [8], Twitter [25,27], and Instagram [10,11]). The increased connectedness between SNSs and applications through SSO buttons provide an abundance of information that can be exploited to implicitly acquire personality traits of users.…”
Section: Related Workmentioning
confidence: 99%
“…These techniques leverage many types of profile data, including social network structure (Staiano et al, 2011) as well as profile activity and interaction patterns (Adali & Golbeck, 2014;Ferwerda, Schedl, & Tkalcic, 2015;Markovikj, Gievska, Kosinski, & Stillwell, 2013). It is especially relevant to this replication that many studies build their models based on analysis of the text users post in their updates (Farnadi, Zoghbi, Moens, & De Cock, 2013;Park et al, 2015;Quercia et al, 2011;Kosinski, Stillwell, & Graepel, 2013).…”
Section: Related Workmentioning
confidence: 99%
“…As a study was done by Ferwerda et al (2015), in which this study explored the personality traits of the users through the picture uploaded correlating to the filter they used. This study found various kinds of picture features by extracting 22,398 pictures from 113 participants and emphasized that there is a relationship between personality traits and the way users want to make their picture look (Ferwerda et al, 2015). It is understood that people will express their personality through pictures edited by some filter features provided by Instagram.…”
Section: Introductionmentioning
confidence: 99%